Implementation of shared care planning in an hospital setting. The experience in Azienda ospedale università di Padova (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The contribution retraces and analyzes the first experiences of shared care planning in the University Hospital of Padua, also in view of law 219/17.
Keywords: Advance care planning; shared care planning; relation; trustee; self-determination; assistance